ANALYSES OF THE IMPACT OF SCHOOL UNIFORMS ON VIOLENCE IN NORTH CAROLINA PUBLIC HIGH SCHOOLS - Johnson, Wesley Scott (East Carolina University, 2010)
This study incorporated a multiple-methods design utilizing both quantitative and qualitative data. The quantitative portion investigated several annual reports distributed by the North Carolina Department of Public Instruction (NCDPI) to explore the impact of school uniform policies on incidents of crime and violence and occurrences of suspensions and expulsions in North Carolina high schools that adopted such policies during the 2004-2005, 2005-2006, 2006-2007, 2007-2008, and 2008-2009 school years. The qualitative portion of this study examined an eight-item researcher-developed Likert-type survey distributed to all current North Carolina administrators working in the high schools where school uniform polices were adopted during the designated time period in an attempt to gauge their perceptions of how the adopted policy had changed the safety of their schools and their campuses.  The data analysis indicated no change to the incidents of crime and violence and occurrences of suspensions for the majority of the thirty-eight high schools being examined in this study, although the school administrators working in these schools perceived school uniforms to positively impact school safety. The data for expulsions had to be omitted due to limited numbers.
Keywords: Education, General; High school students--North Carolina--Uniforms; Dress codes--North Carolina; School discipline--North Carolina; School violence--North Carolina; Public schools--North Carolina